2018
DOI: 10.1159/000499125
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Not Perceiving Family Health History Assessments as Important: Opportunities to Improve Dissemination of Evidence-Based Population Screening for Cancer

Abstract: Introduction: Public willingness to collect personal family health history (FHH) assessments is integral to implement population screening to identify those at high cancer risk who could benefit most from lifesaving interventions. Yet, surprisingly little consideration has been given to factors associated with the public’s perceived importance of FHH in the context of cancer. Methods: Using data from the 2013 Health Information National Trends survey, we assessed the association of intrapersonal (e.g., cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 82 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…30 A recent study also using data from the HINTS 4 Cycle 3 (2013) iteration indicated that those (altogether about one-third) participants who believed that family health history was not important for their health were significantly more likely to be male (57%) than female (43%). 31 Traditional masculinity norms which expect men to be independent and emotionally controlled and regard psychological or medical help-seeking as "weak" or "unmanly" were identified as factors associated with poor communication with health professionals. They also explained delays in medical help-seeking in men in general 32 as well as men's help-seeking for cancer symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 A recent study also using data from the HINTS 4 Cycle 3 (2013) iteration indicated that those (altogether about one-third) participants who believed that family health history was not important for their health were significantly more likely to be male (57%) than female (43%). 31 Traditional masculinity norms which expect men to be independent and emotionally controlled and regard psychological or medical help-seeking as "weak" or "unmanly" were identified as factors associated with poor communication with health professionals. They also explained delays in medical help-seeking in men in general 32 as well as men's help-seeking for cancer symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these findings are the results from the US Health Styles Survey which reported that men are less likely (23%) compared with women (36%) to actively collect health information on their relatives’ health family history 30 . A recent study also using data from the HINTS 4 Cycle 3 (2013) iteration indicated that those (altogether about one‐third) participants who believed that family health history was not important for their health were significantly more likely to be male (57%) than female (43%) 31 …”
Section: Discussionmentioning
confidence: 99%
“…We also asked CHWs in our sample to complete a FHH tool as a means to inform their views about the feasibility of integrating these assessments in their routine practices (Allen, Escoffery, et al, 2018; McWalter & Gaviglio, 2015). CHWs noted that the collection of FHH information would improve their own relationship and work with clients.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, FHH information is collected by health professionals as part of medical visits; however, given the challenges of collecting FHH information in these settings (e.g., limited time, patients having incomplete knowledge of health histories,), a wide range of tools and initiatives have been developed and promoted to facilitate FHH collection outside clinical settings (American Medical Association, 2018; Bates, 2005; Rich et al, 2004; Valdez et al, 2010; Williams et al, 2011). While individuals often recognize the importance of FHH, less than one third of the population has collected personal FHH; FHH knowledge is also notably lower among minorities and those with limited literacy (Allen, Escoffery, et al, 2018).…”
mentioning
confidence: 99%
“…The collection of family cancer history (FCH) is an effective and inexpensive way to capture information that can guide stratified cancer risk assessment, target screening, and prevention efforts; activate individuals and their family members for screening and/or genetic counseling and testing; and motivate positive behavior change (Ashida et al, 2012; Claassen et al, 2010; deHeer et al, 2017; Koehly et al, 2018; McBride et al, 2013; Ochs-Balcom et al, 2015; Qureshi & Kai, 2008; Rebbeck et al, 2018; Valdez et al, 2010; Yoon et al, 2002). While family health history is widely acknowledged as useful for guiding clinical and public health practice, as few as one third of individuals know their family health information and only 3% have ever used a tool to collect this information (C.G. Allen et al, in press).…”
mentioning
confidence: 99%